Importance of Hydrothermal Vents in Scavenging Removal of 230Th in the Nansen Basin. Issue 19 (7th October 2018) - Valk, O.; Rutgers van der Loeff, M. M.; Geibert, W.; Gdaniec, S.; Rijkenberg, M. J. A.; Moran, S. B.; Lepore, K.; Edwards, R. L.; Lu, Y.; Puigcorbé, V.
Abstract: In this study we present dissolved and particulate 230 Th and 232 Th results, as well as particulate 234 Th data, obtained as part of the GEOTRACES central Arctic Ocean sections GN04 (2015) and IPY11 (2007). Samples were analyzed following GEOTRACES methods and compared to previous results from 1991. We observe significant decreases in 230 Th concentrations in the deep waters of the Nansen Basin. We ascribe this nonsteady state removal process to a variable release and scavenging of trace metals near an ultraslow spreading ridge. This finding demonstrates that hydrothermal scavenging in the deep‐sea may vary on annual time scales and highlights the importance of repeated GEOTRACES sections. Plain Language Summary: This study presents new results of thorium isotopes from the central Arctic Ocean. Thorium‐230 is produced continuously in seawater by radioactive decay of 234 U and subsequently removed by particle scavenging. We show that observed changes in 230 Th concentrations compared to earlier times are related to submarine volcanic eruptions. We use 230 Th data from three different expeditions conducted in 1991, 2007, and 2015. The Nansen Basin is part of the Eurasian Basin of the Arctic Ocean. It is divided from the Amundsen Basin by the Gakkel Ridge. The Gakkel Ridge is a region where the Eurasian and the North American plates spread apart, triggering volcanism. Submarine volcanos and hydrothermal vents release trace elements such as iron. Iron is known to be oxidized to particles that react with 230 Th. Thus, when iron particles sink they remove 230 Th from the water column. In the Nansen Basin this process took place between 2007 and 2015, triggered by earthquake‐induced volcanic eruptions in 2001. In this study, we present a conceptual hydrothermal scavenging process and plume dispersal by deep water circulation. Key Point: The first 230Th time series in the Arctic shows that a hydrothermal event caused scavenging removal of 230Th in the Nansen Basin